Upaya Peningkatan Manajemen Proyek Pada CV Nabila Zafira Mahalia Melalui Aplikasi Clickup - Norhikmah Norhikmah; Wiji Nurastuti; Rumini Rumini; Acihmah Sidauruk (Madani : Indonesian Journal of Civil Society, 2023)
At CV. Nabila Zafira Mahali (Nazma) the daily recap of the work of the creative team still uses Google Excel which is prone to data manipulation by people who are irresponsible and don't have a good history of data records, if someone makes a mistake. Recap for monthly reports takes quite a long time, if there is an error in awarding honorarium or there is data that is not appropriate then it is not immediately known by management, the creative team's daily work report has an indirect relationship to the finance department, or the part that regulates awarding honorarium, if the data entered is unclear or inappropriate, there will be a delay in awarding honorarium. Therefore training is needed in using the clickup application which can help the creative team's daily work recap. The process of implementing the training stages begins with an interview with director Nazma and documentation of the required data, followed by determining and creating training materials, and finally, continuing online training using Google Meet, with material using the click-up application, one of the template features, namely CRM (company management profile) in the template there is todo (work list), in progress (under construction), Ready (ready) and complete (finished) features, so that management can monitor the work of the creative team more clearly. In the results of the training evaluation, a score of 70% was obtained on the value of the questions on the benefits of training and project management control.